2010
DOI: 10.3163/1536-5050.98.2.006
|View full text |Cite
|
Sign up to set email alerts
|

Searching for systematic reviews of the effects of social and environmental interventions: a case study of children and obesity

Abstract: Searches for review-level evidence could profitably start with the specialist review databases. Searches of the major health-related databases are essential, but database searching beyond them may not identify much additional evidence. Internet and hand-search remain important sources of reviews not found elsewhere. Comparison of the results with previous research suggests that appropriate sources for locating primary and secondary evidence may be different.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 9 publications
2
16
0
Order By: Relevance
“…Stansfield, Brunton and Rees (2013) examined qualitative reviews on transport, motherhood, and obesity, finding that around a third of the 229 studies would have been missed if only databases had been used, no matter how many were searched. Similar figures were found in: a review deriving 21% of the included publications from citation searching, websites, and hand-searching (Stansfield, Kavanagh, Rees, Gomersall, & Thomas, 2012); a search on childhood obesity where 13% of reviews came from websites, library catalogues, and bibliographies (Woodman et al, 2010); and a review on the built environment where a quarter of studies required specialized sources and grey literature (Weaver et al, 2002).…”
Section: Range Of Search Techniquessupporting
confidence: 55%
“…Stansfield, Brunton and Rees (2013) examined qualitative reviews on transport, motherhood, and obesity, finding that around a third of the 229 studies would have been missed if only databases had been used, no matter how many were searched. Similar figures were found in: a review deriving 21% of the included publications from citation searching, websites, and hand-searching (Stansfield, Kavanagh, Rees, Gomersall, & Thomas, 2012); a search on childhood obesity where 13% of reviews came from websites, library catalogues, and bibliographies (Woodman et al, 2010); and a review on the built environment where a quarter of studies required specialized sources and grey literature (Weaver et al, 2002).…”
Section: Range Of Search Techniquessupporting
confidence: 55%
“…In addition, Woodman et al . () found that specialist review databases including DARE and DoPHER were time efficient places to search for reviews on health inequalities.…”
Section: Methodsmentioning
confidence: 99%
“…Health Technology Assessment database hosted by Centre for Reviews and Dissemination These sources were selected as they are known to have a wide range of up-to-date systematic reviews relevant to public health and health promotion. In addition, Woodman et al (2010) found that specialist review databases including DARE and DoPHER were time efficient places to search for reviews on health inequalities.…”
Section: Research Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…When the topic of study is related to interdisciplinary fields, selection of information source is more difficult ( 1 , 10 - 12 ). Researchers in these fields tend to search several bibliographic databases ( 13 ); for example, Telemedicine is a new issue in health sciences field which is highly related to technology.…”
Section: Introductionmentioning
confidence: 99%